The Impact Of Applying Value Added Tax (VAT) On Cooperate Sales - Alotaibi, Dr Khaled Omair (The journal of contemporary issues in business and government, 2021)
The following study analyses the impact of a multidisciplinary strategy to lower the VAT levels for food classes that equals 15% on the economy. Effects on food market rates, volumes of food demand, government expenditure value-added tax income, consumer and producer gains as well as inflation were evaluated. The effect of the equation decreases the amount of market prices of food by decreasing The Value-Added tax ratio while the reduced estimated price is not commensurate with the decrease in the value-added tax rate. The reduction of the value added tax rate contributes to a marginal rise in sales of food. Simultaneously, decreasing the Value- Added tax ratio lowers VAT income in the government budget, although the overall population income exceeds the reduction a little.